Transverse vibration of thin solid and annular circular plate with attached discrete masses - Ranjan V.; Ghosh M.K. (My University, 2025)
The fundamental frequency of vibration of solid and annular circular plate with different boundary conditions with point mass attached at an arbitrary position using finite element analysis (FEA) was investigated. The FEA method has been employed for modeling the vibration response of the plate and a a system of equations is created, which was solved as an eigenvalue/eigenvector problem. The vibrating coefficients for a rigidly clamped solid circular plates carrying concentrated mass at center was presented. The method was used to present the fundamental frequency coefficients of solid plate with point mass placed at arbitrary positions and of annular plates with point mass placed at outer free boundary with different boundary condition.